KAJIAN STRUKTUR DAN KARIOTIPE GADUNG (Dioscorea bulbifora L.) DI SUMATERA BARAT - Maideliza, Tesri; Dahlan, Sjahridal; Meriko, Lince; Roziah, Roziah; Sari, Eti Sari (UI Scholars Hub, 2007)
The study of anatomical structure and karyotype of West Sumatran Dioscorea bulbifora L. Had been done from March 2005 to January 2006 in plant Structure and Development Laboratory of Biology Department, Faculty of Mathematic and Natural Science, Andalas University. In present study were used descriptives and quantitatives method by preparing semi-permanent and permanent slide. Anatomycal structures of green aerial stem were consisting of epidermal, cortex with endodermoid cells and sclerechima tissue centripetally. Vascular bundle can be rocognized in three distinct rings with amphycribal type. Transverse section of leave anatomical composed by both a layer epidermal on upper and lower leaf surface, palysade parechima, and spons parenchyma (dorsiventral type). The stomata were anomocytic type on both upper and lower surface of leaf (amphystomatic type). Idioblast of cell raphides crystals and tannin containing founded in leaf structure. In transverse section each of eight individual bundle surrounded by sclerenchyma. The root anatomical structures consist of epidermal, cortex, endodermal (U shape wall thickening), pericycle and pith (with three ring of vascular bundles) centripetally. The air tuber lacking of starch grains containing of parenchyma cells. Idioblast cell expected contain of HCN distributed over all of tuber tissue. The somatic cell chromosome were diploid 2n=20 with basic chromosome number were x=10